Structural performance and photothermal recovery of carbon fibre reinforced shape memory polymer - Herath, H.M.C.M.; Epaarachchi, J.A.; Islam, M.M.; Al-Azzawi, W.; Leng, J.; Zhang, F. (Composites science and technology, 2018)
The shape memory polymers (SMPs) have an interesting capability of keeping a temporary shape and then recovering the original shape when subject to a particular external stimulus. However, due to SMP's relatively low mechanical properties, the use of SMP in a wider range of engineering applications is limited. As such SMPs need to be reinforced before use in engineering applications. This paper presents the mechanical properties, thermomechanical characteristics, photothermal behaviour and light activation of 0/90 woven carbon fibre reinforced shape memory epoxy composite (SMPC) made out of prepreg material. Prepreg is a widely used manufacturing technique for large-scale engineering applications. The experimental results have demonstrated that the structural performance of the SMPC has increased significantly due to carbon fibre reinforcement as anticipated. According to ASTM standard D 3039/D 3039M-00, the mode of tensile failure was identified as “XMV”, where the failure is an explosive type. The dynamic mechanical analysis has revealed that the shape fixity and recovery ratios of the SMPC are 100% and 86% respectively. Under the constrained condition, the stress has been recovered up to 5.24 MPa. The SMPC was exposed to five different power densities of 808 nm and the resultant activation has been systematically investigated. Interestingly, the SMPC has been heated over its glass transition temperature, once it is exposed to a power density of 1.0 W/cm2. Furthermore, the applicability of carbon fibre reinforced SMPC for a deployable solar panel array, intended for remote and localized activation is demonstrated. The SMPC will be a potential candidate for space engineering applications, because of its enhanced mechanical properties and ability of photothermal activation.